Cidade Tiradentes e COHAB: moradia popular na periferia da cidade de São Paulo projetos e trajetórias (1960-1980) - Cordeiro, Simone Lucena (2009)
The aim of this piece of work is to capture the orientation of the reasonings and iniciatives related to popular home buildings during the period that goes from the second half of the 1960 s and the late 1980 s in São Paulo, using as focus the department of the town hall that s responsible for the area of the Cidade Tiradentes and the COHAB (aggregation of popular homes). That specific phase has been marked by the creation of the Metropolitan Habitation Company and by one of its major interventions: the building of a COHAB in the neighbourhood called Cidade Tiradentes . Other than that, we believe that our chronological and thematic cutting is justified by the fact that in that same context the ideal of urban planning expanded itself along with the establishment of several organizations, laws and urban and habitation projects. The city went through significant urban and demographic transformations as a result of the great increase in its population and the building of those popular homes in the city outskirts. We assume that the public power sphere lead some of the city s needy population into a process through which their homes were moved more and more to the suburbs, specially by the implantation of projects such as the COHAB built in the Cidade Tiradentes. Nevertheless, we also think that people interacted with the government s actions, (re)creating social and cultural territories and alternative ways of inhabiting the city. In terms of method, along with the official documentation we also used as analysis material some magazines, newspapers, photographs and the personal experience of some inhabitants of Cidade Tiradentes and neighbourhoods alike. We have seeked to build a dialog using the diversity of our literature and other study sources we have collected. We have gone along the building of Cidade Tiradentes, pointing out that it was formed through the government intervention in a context of outskirting of the popular homes. However, we also assume that the locals played main roles in the creation of their own territory and in the conception of their way of life, not always accepted by the township